Site blocking and CO/sulfur site exchange processes on stepped Pt surfaces - Streber, Regine; Papp, Christian; Lorenz, Michael Peter Andreas; Bayer, Andreas; Wickert, Sandra; Schöppke, Matthias; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Physics: Condensed Matter, 2009)
The influence of preadsorbed sulfur on the adsorption of CO on Pt(355) and Pt(322) is investigated systematically for sulfur precoverages between 0.02 and 0.30ML by insitu x-ray photoelectron spectroscopy of the C 1s and S 2p core levels. The two surfaces have the same nominal terrace width of 5 atomic rows, but different step orientation. For both, at low temperatures (130 and 150K), S preferentially adsorbs at the steps and passivates them for COadsorption. The required S precoverage is significantly smaller for Pt(322), because of the lower number of steps as a result of the S-induced double-step formation. Upon heating, population of step sites with CO occurs due to irreversible CO/S site exchange. At low S precoverages, the characteristic transition temperatures of 165K for Pt(355) and 245K for Pt(322) are significantly different, indicating a higher activation barrier for the CO/S site exchange process for Pt(322). For medium to high S precoverages the transition temperature stays unchanged for Pt(322) but increases for Pt(355). The observed behavior is attributed to a kinetic passivation of the steps by sulfur at low temperatures, which is lifted upon heating. © 2009 IOP Publishing Lt